PENAFSIRAN HUKUM HAKIM YANG DIGUNAKAN DALAM MEMUTUS PERKARA KORUPSI BANSOS JULIARI BATUBARA : Judicial Interpretation Used in Deciding the Corruption Case of Social Assistance Funds (BANSOS) of Juliari Batubara - Johannes Agustinus Riady; Abdul Ficar Hadjar (Reformasi Hukum Trisakti, 2024)
Indonesia is one of the countries that adheres to the Continental European Legal System (Civil Law System), where the legal system heavily relies on statutory regulations. However, if the written laws are not found or are insufficient, judges have the authority to interpret the law in deciding a case. In 2020, during the impact of the Covid-19 virus in Indonesia, the Minister of Social Affairs, Juliari Batubara, was implicated in corruption related to the procurement of social assistance funds (bansos) amounting to Rp. 32 billion. The research question to be discussed is what legal interpretation was employed by the judge in deciding the corruption case related to bansos committed by Juliari Batubara (verdict number 29/pid.sus-TPK/2021/PN.JKT.PST). The research method used is normative and analyzed descriptively qualitatively. The research findings indicate that the judge's legal interpretation in deciding this case is based on a comprehensive analysis of each article and written law, correlated with the evidence revealed during the trial. Consequently, in the verdict, the judge has a thorough conviction. The conclusion drawn from this research is that the judge, in deciding the bansos case involving Juliari Batubara, employs a systematic and logical legal interpretation.